In vivo antitumor activity of PHT-427 inhibitor-loaded polymeric nanoparticles in head and neck squamous cell carcinoma - Joaquín Yanes-Díaz; Raquel Palao-Suay; Francisca Inmaculada Camacho-Castañeda; Juan Riestra-Ayora; María Rosa Aguilar; Ricardo Sanz-Fernández; Carolina Sánchez-Rodríguez (Drug Delivery)
Recent studies on head and neck squamous cell carcinoma (HNSCC) tumorigenesis have revealed several dysregulated molecular pathways. The phosphatidylinositol-3-kinase (PI3K) signaling pathway is frequently activated in HNSCC, making it an attractive target for therapies. PHT-427 is a dual inhibitor of PI3K and the mammalian target of AKT/PDK1. This study evaluates the anticancer efficacy of the inhibitor PHT-427 loaded into polymeric nanoparticles (NP) based on α-TOS (NP-427) administered by intratumoral injection into a hypopharyngeal squamous cell carcinoma (FaDu cells) heterotopic xenograft mouse model. The nanocarrier system, based on block copolymers of N-vinylpyrrolidone (VP) and a methacrylic derivative of α-TOS (MTOS), was synthesized, and PHT-427 was loaded into the delivery system. First, we evaluated the effect of NP-427 on tumor growth by measuring tumor volume, mouse weight, survival, and the development of tumor ulceration and necrosis. In addition, we measured PI3KCA/AKT/PDK1 gene expression, PI3KCA/AKT/PDK1 protein levels, Epidermal Growth Factor Receptor (EGFR), and angiogenesis in the tumor tissue. PHT-427 encapsulation increased drug efficacy and safety, as demonstrated by decreased tumor volume, reduced PI3K/AKT/PDK1 pathway expression, and improved antitumor activity and necrosis induction in the mouse xenograft model. EGFR and angiogenesis marker (Factor VIII) expression were significantly lower in the NP-427 group compared to other experimental groups. Administration of encapsulated PHT-427 at the tumor sites proves promising for HNSCC therapy.